Textile electrodes embedded in clothing: A practical alternative to traditional surface electromyography when assessing muscle excitation during functional movements - Colyer, S. L.; McGuigan, P. M. (Journal of Sports Science & Medicine, 2018)
Textile electromyography (EMG) electrodes embedded in clothing allow muscle excitation to be recorded in previously inaccessible settings; however, their ability to accurately and reliably measure EMG during dynamic tasks remains largely unexplored. To quantify the validity and reliability of textile electrodes, 16 recreationally active males completed two identical testing sessions, within which three functional movements (run, cycle and squat) were performed twice: once wearing EMG shorts (measuring quadriceps, hamstrings and gluteals myoelectric activity) and once with surface EMG electrodes attached to the vastus lateralis, biceps femoris and gluteus maximus. EMG signals were identically processed to provide average rectified EMG (normalized to walking) and excitation length. Results were compared across measurement systems and demonstrated good agreement between the magnitude of muscle excitation when EMG activity was lower, but agreement was poorer when excitation was higher. The length of excitation bursts was consistently longer when measured using textile vs. surface EMG electrodes. Comparable between-session (day-to-day) repeatability was found for average rectified EMG (mean coefficient of variation, CV: 42.6 and 41.2%) and excitation length (CV: 12.9 and 9.8%) when using textile and surface EMG, respectively. Additionally, similar within-session repeatability (CV) was recorded for average rectified EMG (13.8 and 14.1%) and excitation length (13.0 and 12.7%) for textile and surface electrodes, respectively. Generally, textile EMG electrodes appear to be capable of providing comparable muscle excitation information and reproducibility to surface EMG during dynamic tasks. Textile EMG shorts could therefore be a practical alternative to traditional laboratory-based methods allowing muscle excitation information to be collected in more externally-valid training environments.